4(3x+12)=2(2x+4)

Simple and best practice solution for 4(3x+12)=2(2x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+12)=2(2x+4) equation:


Simplifying
4(3x + 12) = 2(2x + 4)

Reorder the terms:
4(12 + 3x) = 2(2x + 4)
(12 * 4 + 3x * 4) = 2(2x + 4)
(48 + 12x) = 2(2x + 4)

Reorder the terms:
48 + 12x = 2(4 + 2x)
48 + 12x = (4 * 2 + 2x * 2)
48 + 12x = (8 + 4x)

Solving
48 + 12x = 8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
48 + 12x + -4x = 8 + 4x + -4x

Combine like terms: 12x + -4x = 8x
48 + 8x = 8 + 4x + -4x

Combine like terms: 4x + -4x = 0
48 + 8x = 8 + 0
48 + 8x = 8

Add '-48' to each side of the equation.
48 + -48 + 8x = 8 + -48

Combine like terms: 48 + -48 = 0
0 + 8x = 8 + -48
8x = 8 + -48

Combine like terms: 8 + -48 = -40
8x = -40

Divide each side by '8'.
x = -5

Simplifying
x = -5

See similar equations:

| 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 | | 6x+35=15x-55 | | 5a-3-4a+3=8 | | (4x^2+3x+5)-(6x^2-8)= | | 6a-2-5a+2=-2 | | X^2+17x=-72 | | -4a+3a-6=-4 | | 9x-19=5x+12 | | 6q-9=4q-19 | | c-5*4=-48 | | 4x+5=24 | | 6x-4=3x+2 | | 142-5x=40x+22 | | 5y-13=3y+1 | | 1+3=x | | 12-10x=46-24x | | 12x^3-6x^2-24x+18=0 | | 145=5v | | 1+3=,x | | 4v+9=7v-21 | | (3m+1)(m+5)= | | 2t^2-7t+6=0 | | z^3+8i=0 | | -10-2x=8-8x | | 12+9=7v-21 | | r+2*-3=-6 | | 5(x-3)-3(4-2x)=3-5(8-3x) |

Equations solver categories